Pengaruh Kenaikan Tarif Dan Literasi Pajak Pertambahan Nilai (PPN) Terhadap Tingkat Kepatuhan Wajib Pajak Badan Di KPP Pratama Malang Selatan - Amalia Hidayati; Untung Wahyudi; Khojanah Hasan (CV. ITTC INDONESIA, 2025)
The increase in the Value Added Tax (VAT) rate from 11% to 12%, effective from January 1, 2025, is a continuation of a previously initiated tax policy. This VAT rate hike is considered to affect VAT literacy and corporate taxpayer compliance, as it can create a perception of an increasing tax burden and may reduce the income received by corporate taxpayers. Therefore, this study aims to examine the effect of the rate increase and VAT literacy on the compliance level of corporate taxpayers at the Pratama Tax Service Office (KPP) in South Malang. This study adopts a descriptive quantitative approach. The population for this research consists of corporate taxpayers registered as Taxable Entrepreneurs (PKP), based on data from the KPP showing there are 130 corporate taxpayers with normal status. The sample was determined using a non-probability sampling method, specifically purposive sampling, resulting in 100 respondents who became the research sample. Primary data was obtained from online questionnaires. The analysis technique used in this study is multiple linear regression analysis. Based on the analysis results, it was concluded that the rate increase has a significant negative effect on the compliance level of corporate taxpayers, while VAT literacy has a significant positive effect on the compliance level of corporate taxpayers. Furthermore, the rate increase and VAT literacy simultaneously and significantly influence the compliance level of corporate taxpayers.